Plasmid-Curing, Antimicrobial, Antioxidant Properties and Phytochemical Analysis of Medicinal Plants from North East India: Pharmaceutical Science-Microbiology for Traditional Medicine - Aparna Gunjal; Rajashree Patwardhan; Aditi Jedhe; Vaishnavi Choudhary (International Journal of Life Science and Pharma Research, 2022)
The medicinal importance of plants is in their bioactive substances which exert definite physiological action on the human body. In the present investigation antimicrobial activities of Garcinia pedunculata, Phlogacanthus thyrsiformis, and Ziziphus mauritiana were studied against microbial strains using agar disc diffusion. In-vitro phytochemical screening for chloroform, isoamyl alcohol and water extracts of parts of plants was performed. For MIC (minimum inhibitory concentration), grid method was used. The antioxidant activity of the plant extracts was studied using the ferric reducing antioxidant method and bioautography was studied using Thin Layer Chromatography (TLC). Garcinia pedunculata and Phlogacanthus thyrsiformis extracts showed highest antimicrobial activity. In-vitro phytochemical screening for chloroform, isoamyl alcohol and water extracts of parts of plants showed positive results for alkaloids, saponins, steroids, triterpenes, flavonoids and diterpenes. The MIC value of Garcinia pedunculata, Phlogacanthus thyrsiformis and Ziziphus mauritiana was 2560, 1280 and 2560 µL, respectively. The antioxidant activity revealed that there was an increase in absorbance with the increase of sample concentration. In Thin Layer Chromatography-Bioautography, chloroform extract of Garcinia pedunculata and Ziziphus mauritiana showed activity with zones of inhibition on bioautograms. The chloroform extract of Ziziphus mauritiana was found to be effective with curing efficiency for E. coli K12 (RP4), E. coli (pBR322) and E. coli (pRK2013) 62%, 57% and 49% respectively. Petroleum ether extract of Phlogacanthus thyrsiformis cured E. coli K12 (RP4), E. coli (pBR322) and E. coli (pRK2013) at 38%, 42% and 35% curing efficiencies respectively. This is the first report of plasmid curing by using chloroform Ziziphus mauritiana and petroleum ether extract of Phlogacanthus thyrsiformis. The present investigation has revealed applications and significance of plant extracts of Garcinia pedunculata, Phlogacanthus thyrsiformis, and Ziziphus mauritiana as plasmid curing, antimicrobial and antioxidant agents to control infections and spread of antibiotic resistance in pathogenic bacteria.